The correlation between junior high school students' level of physical fitness and their level of healthy lifestyle - Melly Nova Anggraeni; Sumbara Hambali; Akhmad Sobarna (Universitas Negeri Malang, 2024)
Background: Research on the relationship between physical fitness and a healthy lifestyle has become widespread, and most studies show that the two are related. However, these studies still indirectly examine the relationship between physical fitness and a healthy lifestyle, especially in junior high school students. Objective: This research aims to determine whether there is a relationship between physical fitness and the level of a healthy lifestyle. Methods: This research uses a quantitative descriptive method with a correlational design. This research used the population of the author, which was all eighth-grade students at Negeri 6 Cimahi Junior High School; there were ten classes totaling 380 students. The sample was eighth-grade students from 10 Cimahi 6 State Junior High School classes, with 37 students. The research instruments chosen were questionnaires for healthy lifestyles and the TKSI (Indonesian Student Fitness Test) for physical fitness. The IBM SPSS version 26 software was used to help with the data analysis in this investigation. Result: The correlation study results between physical fitness and the degree of a healthy lifestyle revealed a substantial positive association between the two, with a p-value of 0.007 < 0.05 and a correlation coefficient of 0.434 in the medium category. Conclusion: Based on the research results, the author can conclude that there is a relationship between physical fitness and a healthy lifestyle and the level of a healthy lifestyle in junior high school students. This research implies that programs regarding healthy lifestyles must be given to students, so it is hoped that students will have good physical fitness.